The trauma of Nineveh"s demise and downfall: Nahum 2:2–11 - Wessels, Wilhelm J. (HTS teologiese studies, 2020)
Trauma is left, right and centre in the whole book of Nahum. The book reflects the oppression and hardship that Judah had experienced at the hands of the imperial power Assyria. For many a reader, the violent and derogative content of this book is in itself a traumatic experience. In this article, the focus is on Nahum 2:2–11 (Masoretic Text [MT]), which depicts the downfall of Nineveh and its traumatic effects on its citizens. Besides the analysis of the text, a reading from trauma theory is made to enhance insights into the text. It is argued that the text served the purpose of offering hope to the people of Judah who relied on Yahweh for relief from their own traumatic experiences.